MENUJU LINGKUNGAN SEHAT: INOVASI PENGELOLAAN SAMPAH DI DESA NAGROG - Siti Nur; lilis suwandari; Muhamad Sopyan Syauri N, MZ; Ramdhan Hendrawan; Mukhlis Aburizal Khordowi; Fauzan Rizky Gunawan (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2025)
This study aims to explore the effectiveness of waste management innovations through the provision of specific trash bins and sorting practices in Nagrog Village, as an effort to mitigate the high volume of waste and low public awareness. The primary motivation for this study was to create a healthy and clean environment without relying on composting, while still increasing community participation in waste management. The methodology involved field observations, interviews with residents and village leaders, and the collection of quantitative data related to the volume and frequency of waste collection. The intervention focused on establishing separate trash bins (organic, inorganic, and residual) at strategic points in the village and educating the community about individual waste sorting. This practice aligns with similar models in other villages, such as Tenjolayar and Latsari, which focus on sorting with specific bins. The results showed significant improvement, as points that were usually filled with trash have now begun to decrease. This improvement indicates that the provision of special bins and intensive education can significantly improve environmental cleanliness, even without further waste processing. The researchers concluded that this simple model is effective for villages with limited resources. Sustainable success depends on consistent education, local government support for collection facilities, and the possibility of developing further schemes for organic and inorganic waste in the future.